Integrating the 5A Framework within Community-Based Tourism: A Case Study of Hanjeli Tourism Village, Indonesia - Endah Djuwendah; Elly Rasmikayati; Bobby Rachmat Saefudin (Global Review of Tourism and Social Sciences, 2025)
This study integrates the 5A framework, Attraction, Accessibility, Amenities, Accommodation, and Activities within a community-based tourism (CBT) approach to evaluate the development readiness of Hanjeli Tourism Village in Sukabumi, Indonesia. Using a mixed-methods design, data were collected from a survey of thirty tourists, field observations, and interviews with key local stakeholders. Quantitative results reveal that attractions, activities, and community-based accommodations are the village’s primary strengths, characterized by authentic agro-tourism centered on hanjeli (Coix lacryma-jobi), participatory learning experiences, and meaningful host–guest interaction. Conversely, accessibility and amenities remain critical challenges due to narrow roads, limited transportation, and insufficient visitor facilities. Qualitative findings highlight that while the village’s authenticity enhances visitor satisfaction, infrastructural constraints hinder its broader competitiveness. The integration of the 5A model with CBT principles offers a comprehensive analytical perspective that captures both tangible and intangible aspects of rural tourism development. The study contributes theoretically by extending the 5A framework to a community-driven context and practically by identifying strategies for improving infrastructure, service quality, and digital promotion. Overall, Hanjeli Tourism Village exemplifies how local participation and cultural heritage can drive sustainable rural tourism when supported by balanced infrastructural and managerial development.